THE EFFECT OF MACKEREL (Scomberomorus commerson) IN THE FEED TO THE DECLINE IN BLOOD CHOLESTEROL LEVEL HYPERCHOLESTEROLEMIC MALE MICE (Mus musculus) - Rudi Kartika; Djihan Ryn Pratiwi; Arifwan -; Wahyu Budi Utama; Wahyu Teguh Santoso (PROSIDING SEMINAR KIMIA, 2014)
Blood cholesterol levels wh ich were higher than normal is trigger of various diseases. The objective of the research was to know “The Effect of Mackerel (Scomberomorus co mmerson) in the Feed to the Decline in Blood Cholesterol Levels in Hypercholesterolemic Male Mice (Mus musculus). The study was conducted over 40 days using completely randomized design with treatments, the positive control, negative control, and the mice were given the addition of mackerel on a standard feed with 3 different levels so grouped in L1 (2:1); L2 (1:1) and L3 (1:2). The parameters measured are total cholesterol blood serum of mice with the CHOD-PAP method. Cholesterol levels are measured with a photometer 5010 at a wavelength of 500 nm. The result in the (-) 86 mg/d L; (+) 113 mg/d L; L1 102 mg/d L; L2 86 mg/dL; and L3 82 mg/dL.